2018
DOI: 10.3390/su10051552
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Evolution of Convergence in the EU? Decomposing EU Disparities up to NUTS 3 Level

Abstract: Research on convergence deals with the question of whether regional disparities are decreasing over time. Aiming to decompose EU disparities covering regions of all levels, this paper fills the gap of the empirical research on convergence in the EU in the following ways: (i) the research updates the assessment of regional disparities in the EU emphasizing, but not limited to, the analysis at the NUTS 3 level; (ii) based on a constructed three-level Theil index, the research decomposes EU disparities into betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 40 publications
6
47
0
2
Order By: Relevance
“…As the dependent variable, we used annual growth of per capita GDP and GVA per person employed at the NUTS 2 and 3 disaggregation level as a proxies for economic growth and productivity growth at the regional level, ascertaining all shortcomings of this approach discussed in Butkus et al [63], among many others. For the detailed explanation of the dependent variable and data source for Y i,t , see Appendix C.1.…”
Section: Methodsmentioning
confidence: 99%
“…As the dependent variable, we used annual growth of per capita GDP and GVA per person employed at the NUTS 2 and 3 disaggregation level as a proxies for economic growth and productivity growth at the regional level, ascertaining all shortcomings of this approach discussed in Butkus et al [63], among many others. For the detailed explanation of the dependent variable and data source for Y i,t , see Appendix C.1.…”
Section: Methodsmentioning
confidence: 99%
“…In their paper, they used the empirical shrinkage Bayesian estimator. But to attempt our main goal which is to compare the convergence path, we decide to use the simple and traditional approach of ordinary least square (OLS) estimator (see Maddala and Wu, 2000, p.638;Butkus et al, 2018). Despite some bias which can be associated with this method, we believe that it is not a great concern which can affect the order of estimates since values of estimates from Bayesian approach for this study seem to be similar to those of the OLS.…”
Section: Methodsmentioning
confidence: 99%
“…They proposed a detection of convergence clubs based on spatial analysis where each club has its own steady state based on regional factors. Butkus et al (2018) have shown the paradox of convergence in European regions. They find absolute convergence occurring in European countries.…”
Section: Business and Economic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if the scope is changed, the convergence observed between EU Member States sometimes actually masks an increase in regional intra-state inequalities. Convergence phenomena observed at NUTS 3 level produce either convergence or divergence locally (Bourdin, 2015;Butkus et al, 2018). Some studies have particularly highlighted a quick growth recorded in metropolitan regions due to a concentration of service activities, direct foreign investment, and a significant number of start-up launches.…”
Section: Territorial Inequalities That Are Not Always Visiblementioning
confidence: 99%